Risk Analysis of Operation Igniter Technology System For Rocket Motor X - Nugroho, Widianto; Tjahjadi, Hendrana; Yogaswara, Y. H.; Lestariana, Evie (Indonesian Journal of Aerospace, 2022)
This study discusses risk assessment, and the results of the analysis on the ignition system used on the X rocket. The purpose of this study was to obtain a risk analysis obtained when operating the ignition system on the X rocket. This study used HIRADC (Hazard Identification, Risk Assessment and Determining Control) with a qualitative explanation. The results of the risk assessment in the X rocket motor testing process on the application of the ignition system, there are 10 risks in activities consisting of 8 activities that have a "low" risk level, while the other 2 have a "High" risk level. Caused by probability 1 and severity 4 which can result in device explosion as well as death of the user. The scope of the next assessment is instruments risk assessment, based on the research conducted, the results obtained from the risk assessment are 13 risks of instruments failure, consisting of 9 risks with a "low" risk value. Meanwhile, there are 2 "moderate" risks, namely a short circuit in the cable and the casing does not catch fire which can result in serious injury. Other sectors that have 2 high risk "High" are found to be at risk of not being grounded which can result in static electricity not going to ground, premature ignition during installation, explosion, which can cause death.